Adjudication practice and procedure in Ireland : Construction Contracts Act 2013 - Keogh, Damien (Lawyer); Lawless, Niall; Ireland (Abingdon, Oxon ; New York, NY : Routledge, 2020)
This adjudication textbook uniquely brings together a comprehensive analysis of, and commentary on, the Construction Contracts Act 2013 with a real-world perspective of adjudication, considering the knowledge, process and skills parties and adjudicators require in order to successfully participate in the adjudication process. Drawing on combined experience of 40 years in construction law, the authors provide invaluable guidance for all stakeholders in the adjudication process. The authors analyse and comment on the adjudication provisions of the Construction Contracts Act and describe prudent practice and procedure required to comply with Irish adjudication law, including case studies, case law and sample documentation for those to be involved as the parties, or those who want to act as adjudicators. Aimed at contractors, sub-contractors, developers, employers, construction, engineering and legal professionals and students, all of whom are either involved, or have an interest, in dispute resolution and adjudication.
Introduction -- Overview of the Construction Contracts Act -- What constitutes a construction contract? -- Exempted contracts -- Right to refer payment related disputes to adjudication -- Adjudicator appointment -- Referral to the adjudicator -- Timing of the adjudicator's decision -- The adjudicator's role, responsibilities, and powers -- Content and enforceability of the adjudicator's decision -- Costs of adjudication -- Code of practice governing the conduct of adjudications -- Service of notices -- Enforcing the adjudicator's decision -- Knowledge -- Process -- Skills.
OCLC-licensed vendor bibliographic record.
Keywords: Construction contracts -- Ireland; Arbitration and award -- Ireland; Ireland; TECHNOLOGY / Construction / General